2015
DOI: 10.3892/or.2015.4143
|View full text |Cite
|
Sign up to set email alerts
|

Twist induces epithelial-mesenchymal transition in cervical carcinogenesis by regulating the TGF-β/Smad3 signaling pathway

Abstract: Epithelial-mesenchymal transition (EMT) is associated with the metastasis and poor prognosis of cervical cancer. However, the underlying mechanisms are poorly defined. In the present study, we investigated whether Twist plays a direct role in human cervical cancer using immunohistochemical and western blot analyses. Immunohistochemical analysis revealed that Twist is highly expressed in cervical cancer, which correlates with poor tumor pathological differentiation or lymph node metastasis (P<0.05). Depletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…Recent studies have shown that activation of TGFA/Smad3 signal can induce the migration and invasion of cervical cancer cell lines, suggesting that it plays a vital role in cervical cancer metastasis. 32 These results are consistent with our findings that miR-195 level negatively correlates with advanced clinical stage and lymphatic metastasis of cervical cancer and that Smad3 is a functional target of miR-195. We showed that overexpression of Smad3 abrogated tumor suppressive effects of miR-195 on cervical cancer cell migration and invasion.…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies have shown that activation of TGFA/Smad3 signal can induce the migration and invasion of cervical cancer cell lines, suggesting that it plays a vital role in cervical cancer metastasis. 32 These results are consistent with our findings that miR-195 level negatively correlates with advanced clinical stage and lymphatic metastasis of cervical cancer and that Smad3 is a functional target of miR-195. We showed that overexpression of Smad3 abrogated tumor suppressive effects of miR-195 on cervical cancer cell migration and invasion.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with the results of Meng et al ., we observed that the knockdown of PODXL expression inhibited TGF‐β‐induced EMT of A549 cells (data not shown). Although many transcript factors, including Snail and Twist, are known to regulate EMT, immunoblotting did not reveal upregulation of Snail or Twist in PODXL‐OE cells. However, EMT was induced by PODXL expression, as shown by changes in EMT markers, including E‐cadherin, N‐cadherin, vimentin, fibronectin and αSMA.…”
Section: Discussionsupporting
confidence: 92%
“…Cervical cancers can be further classified to the well, moderately and poorly differentiated subtypes (Yoo et al, ). The poorly differentiated CCs usually grow more aggressively and lead high metastatic rates because of their strong EMT tendency (Miao et al, ; Fan et al, ). We therefore analyzed the relevance of S100A4 upregulation and membrane E‐cadherin reduction with the grades of CCs.…”
Section: Discussionmentioning
confidence: 99%